Interictal language functions in temporal lobe epilepsy. Issue 6 (16th May 2005) - Bartha, L; Benke, T; Bauer, G; Trinka, E
Abstract : Objective: To evaluate interictal language functions in patients with medically intractable left and right sided mesial temporal lobe epilepsy (TLE). Methods: Spontaneous speech, language comprehension, confrontation naming, repetition, reading, writing, and word fluency were examined in 12 patients with left sided TLE and 11 patients with right sided TLE. Results: Four patients out of 23 displayed language deficits in more than one language domain. Three further patients exhibited isolated language deficits. Linguistic deficits were observed in both left TLE and right TLE. In quantitative analyses left and right TLE only differed in spontaneous speech (p = 0.02); no difference was found in other language functions, laterality quotient of Wada test, or overall IQ. Qualitative error analysis of object naming, however, showed typical errors associated only with left TLE. Patients with linguistic deficits were older at testing compared to patients without linguistic deficits (p = 0.003), whereas other factors including side of TLE, handedness, educational level, age at epilepsy onset, and duration of epilepsy did not differ between groups. Conclusions: Possible explanations for these findings include neuronal cell loss and deafferentiation in cortical areas, and disruption of the basal temporal language area pathways. Our study suggests that some patients with chronic mesial TLE exhibit linguistic deficits when specifically tested, and underlines the need to routinely investigate linguistic functions in TLE.